RESTORATIVE JUSTICE APPROACH IN THE SETTLEMENT OF CHILDREN’S CASES IN INDONESIA - Sirait, Trinita Yulinda; Cahyaningtyas, Irma (Legality : Jurnal Ilmiah Hukum, 2019)
Restorative justice is a way to resolve criminal cases involving the community, victims, and perpetrators of crime to achieve justice for all parties so that it is expected to create the same conditions as before the crime and prevent further crime. However, implementation is often overlooked in children who commit crimes. The research method used in this study is the normative legal research method with the legislation approach and conceptual approach. This research shows the case of children before the law (ABH) brought in the judicial process must always prioritize the principle of the best interests of children, and the process of punishment is a last resort. Cases can be resolved through informal mechanisms based on standard guidelines. This form of informal handling can be done by diversion through a mediation process facilitated by law enforcement at every level to achieve restorative justice through diversion. Thus, the core of restorative justice is healing, moral learning, community participation and attention, dialogue, forgiveness, responsibility and making changes, all of which are guidelines for the recovery process in the perspective of restorative justice.